Digital Transformation of Electronic Land Certificates : Solutions and Challenges in Indonesia's Modern Land Registration System - Putu Agus Susila Adnyana; I Ketut Kasta Arya Wijaya (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Digital transformation in land administration is a strategic step by the Indonesian government to realize a more efficient, transparent, and secure land registration system. One concrete form of this transformation is the implementation of electronic land certificates (e-certificates) regulated in the Ministerial Regulation of ATR/BPN No. 1 of 2021. This article aims to analyze the implementation of electronic land certificates as a legal innovation in the national land registration system and examine the challenges and solutions faced in its implementation. Using a normative juridical approach supported by literature studies and analysis of laws and regulations, this article finds that e-certificates have a strong legal basis and great potential in reducing agrarian conflicts, accelerating the registration process, and strengthening legal protection of land rights. However, its implementation is still faced with structural obstacles, such as limited information technology infrastructure, low digital literacy of the community, and resistance to system changes. Therefore, a strong policy commitment, an inclusive implementation strategy, and strengthening regulations and institutions are needed to ensure the success of the digitalization of the land system in Indonesia. Electronic land certificates are not only an administrative tool, but also a symbol of legal reform and equitable land governance in the digital era. Furthermore, enhancing public awareness and education regarding e-certificates is crucial to foster acceptance and understanding among stakeholders. Engaging various community groups in the digital transformation process can also facilitate smoother transitions and promote a culture of innovation in land administration. Ultimately, the successful implementation of e-certificates can serve as a model for other sectors undergoing digital transformation in Indonesia.